BIODIVERSITAS GASTROPODA DI PERSAWAHAN KANDARA KECAMATAN KAMBERA KABUPATEN SUMBA TIMUR - Sriratna Maramba Awang; Erfy Melany Lalupanda; Anita Tamu Ina (Fakultas Sains dan Teknologi, Universitas Islam As-Syafi'iyah, 2023)
This study aims to determine the level of gastropod diversity in Kandara Rice Fields,. This research is an ecological research with a quantitative approach. This study uses a quadratic transect method and sampling using the purposive sampling method. The gatropoda found were Pomacea canalicuta, Melanoides tuberculata, Achatina fulicia, which consisted of 2 orders (Mesogastropoda and Pulmonata), 3 families (Ampullaridae, Thiaridae, and Achatiniadae), 3 genera (Pomacea, Melanoides, and Achatina). The results of the calculation of the ecological index showed that the highest species abundance index was Pomacea canalicuta species with a total of 138 while the lowest species abundance was Achatina fulicia with a number of 12 and a relative abundance of 10.00%, which means it has a low abundance level. The dominance index is 0.50 which means it is in the medium category. The diversity index is 0.81which means the level of diversity is low.